Perencanaan dan Implementasi Sistem Informasi Manajemen Penjualan Berbasis CMS WordPress (Studi Kasus di CV Nugarada Abadi) - Shinta Aprillia; Sholihati Amalia (Ebiz Prima Nusa, 2022)
Sales management information system or commonly abbreviated as sales MIS is an important function needed on a site company. Based on the identification of problems in CV Nugarada Abadi, one of the problems at the company is the official website which is not equipped with a sales MIS. Therefore, the owner plans to make the company's official website a means of buying and selling transactions. Based on the WordPress CMS, the site was originally created only for the requirements of an auction procurement project, but now with the development of technology, many competitors are already using the company's website as a means of buying and selling transactions. The sales MIS is made according to the company's needs which includes the processing of goods, ordering, payment, and delivery. Black Box method and questionnaires are used to evaluate both in terms of sales MIS and in terms of users. The results of the implementation of this project facilitate the work of the CEO in monitoring sales history, the work of the sales department because all data is stored in the database, and benefits the company because it can increase revenue by transacting on the CV Nugarada Abadi website.